Therapeutic effects of black cumin (Nigella sativa). A systematic review - Perveen, Rashida (Progress in Nutrition, 2019)
Functional foods are predicted to become one of the prime dietary trends in the incoming decades and it is the responsibility of the nutritionists to pay attention towards their health claims and safety issues. Black cumin (Nigella sativa L.) locally known as “Kalonji” is a good source of nutritionally essential components. Their seeds have been used as herbal medicine by various cultures and civilizations to treat and prevent a number of diseases. Consumption of antioxidant rich foods may improve antioxidant defense mechanism and provide protection against oxidative damage caused by free radicals. In this context, black cumin is used against cancer, diabetic, antifungal, antibacterial and antioxidant. It has been realized that diet-based therapies are among the most effective and sustainable ways to overcome various maladies. It is deduced that black cumin fixed can be supplemented in food products for the management of these maladies. The health benefits including amelioration of oxidative stress, hypoglycemic and hypocholesterolemic potentials associated with the consumption of black cumin seed